All Days 2004
DOI: 10.2118/88751-ms
|View full text |Cite
|
Sign up to set email alerts
|

South-Pars Phases 2 and 3: The Kinetic Hydrate Inhibitor (KHI) Experience Applied at Field Start-up

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSouth-Pars Phases 2&3 development in Iran is a "wet scheme" base design: no process is performed offshore, all the produced fluids (sour gas + condensate + water) are directly sent to shore through two 32" 109 km long sea lines. Corrosion and hydrate protection is based on buffered glycol (MEG+MDEA) which is regenerated onshore and sent back to the platforms through two 4½" piggyback lines.The concomitant injection of a Kinetic Hydrate Inhibitor (KHI) and a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…In our previous studies, , we have conducted several similar experiments and have found a similar variation in the results with variations around ± 5–15%. A similar variation in results has been observed by several other researchers. , Therefore, we can expect a similar 5–15% variation in all the results reported in this study.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…In our previous studies, , we have conducted several similar experiments and have found a similar variation in the results with variations around ± 5–15%. A similar variation in results has been observed by several other researchers. , Therefore, we can expect a similar 5–15% variation in all the results reported in this study.…”
Section: Methodssupporting
confidence: 93%
“…Kinetic hydrate inhibitors (KHIs) are water-soluble polymers that offer cost- and environmentally effective alternatives to THIs since they are effective at very low polymer dosages (0.5–2 wt %) of the water content. Because of this, KHIs are gradually gaining popularity as a method of hydrate inhibition and are being investigated by several researchers. KHIs delay the formation/nucleation of hydrates and some even slow the hydrate crystal growth. , However, they can not inhibit hydrate formation indefinitely. Morever, after a certain threshold supercooling/subcooling, depending on the type of hydrate structure (Δ T > 7 K for sI hydrates and Δ T > 12 K for sII hydrates), the use of KHIs at typical concentrations of usage around 0.5–1 wt % becomes ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…If the contents of hydrocarbon multiphase pipelines are at thermodynamically favourable conditions (low temperatures and high pressures), hydrate crystal formation may occur . The solid hydrate particles may aggregate with time and can then block the flow .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike THIs, kinetic hydrate inhibitors (KHIs), can provide effective hydrate avoidance at dosages of a few percent. These chemicals are one of the two classes of low dosage hydrate inhibitors (LDHIs) which are used at concentrations an order of magnitude lower than that needed for THIs [5,7,8]; they thus have the potential to offer cost savings [8] and/or increase development viability. However, KHIs do not strongly modify the boundary of the hydrate stability region [9].…”
Section: Introductionmentioning
confidence: 99%